2018
DOI: 10.1172/jci98215
|View full text |Cite
|
Sign up to set email alerts
|

Specialized fibroblast differentiated states underlie scar formation in the infarcted mouse heart

Abstract: Fibroblasts are a dynamic cell type that achieve selective differentiated states to mediate acute wound healing and long-term tissue remodeling with scarring. With myocardial infarction injury, cardiomyocytes are replaced by secreted extracellular matrix proteins produced by proliferating and differentiating fibroblasts. Here, we employed 3 different mouse lineage-tracing models and stage-specific gene profiling to phenotypically analyze and classify resident cardiac fibroblast dynamics during myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
522
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 505 publications
(567 citation statements)
references
References 48 publications
41
522
3
1
Order By: Relevance
“…were PDGFRα bright αSMA -, as expected of resting fibroblasts. Post-MI, the infarct region contained abundant, large, tdTomato + PDGFRα dim αSMA high cells, findings consistent with recent fibroblast lineage tracing studies [34][35][36] .…”
Section: Pdgfra-gfp Discriminates Between Resting and Activated Fibrosupporting
confidence: 88%
“…were PDGFRα bright αSMA -, as expected of resting fibroblasts. Post-MI, the infarct region contained abundant, large, tdTomato + PDGFRα dim αSMA high cells, findings consistent with recent fibroblast lineage tracing studies [34][35][36] .…”
Section: Pdgfra-gfp Discriminates Between Resting and Activated Fibrosupporting
confidence: 88%
“…Thbs4 more closely resemble matrifibrocytes that reside in a mature scar after MI[15]. Although expression of key matrifibrocyte marker genes-Comp, Sfrp2 or Wisp2-were not highly enriched in cells defined as Fibroblast-Cilp and Fibroblast-Thbs4 in this study, the functional inferences made of these cell populations are comparable.…”
contrasting
confidence: 50%
“…Finally, in accordance with transcriptomic analyses, we confirmed that neither Fibroblast-Cilp nor Fibroblast-Thbs4 correspond to ACTA2 + myofibroblasts ( Figure 4G and H) using mice from two independent mouse colonies. These findings suggest that Fibroblast-Cilp and Fibroblast-Thbs4 may be transcriptionally similar to the matrifibrocyte, a specialized fibroblast state found in the mature scar after MI [15]. While Fibroblast-Cilp/Thbs4 had some expression of the matrifibrocyte markers Comp, Sfrp2, and…”
Section: Indeed Examination Of Total Transcripts Corresponding To Ecmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent study has defined the CF response after MI using three different mouse models of cell lineage tracing 31 . The results of this study, based on stage specific transcriptomics, suggest a model of CF kinetics that includes the initial proliferation followed by activation and migration of CF and eventually the conversion of these activated CF into non-proliferating, matrixproducing fibroblast named "matrifibrocytes" 31 . IRCF show a similar transcriptional signature and anatomical location into the fibrotic scar to "matrifibrocytes" ( Fig.…”
Section: Discussionmentioning
confidence: 99%